Fostering EFL Learner Autonomy in Indonesian Context - Muhamad Ahsanu (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2017)
Every teaching practitioner seemingly has come to a common term that language advising is essential in language learning especially in fostering language learner autonomy. However, the issues as to whether teachers also serve as advisors or advisors are also teachers, or whether both play separate roles, or they are actually the same individuals who play different roles are still in controversy. This writing is not trying to claim which one is right and which one is not. This essay is just a little lantern on how actually the roles of advisors are exercised by teachers within the context of Indonesian EFL classrooms. Presumably, the advising teachers in Indonesian setting do not only feel responsible for transmitting knowledge and skills, but also for transforming ideas, advice, morality, values, etc. into their learners within and beyond classroom practices. Thus, the inkling of this essay is briefly addressing both theoretical and practical account of language advising within the spectrum of learner autonomy.